Guangdong's experience in defeating the COVID-19. Issue 18 (7th May 2021) - Chen, Haiqian; Shi, Leiyu; Zhang, Yuyao; Wang, Xiaohan; Sun, Gang
Abstract : Abstract: To provide valuable experience for other countries currently fighting the COVID-19 pandemic by systematically analyzing the effects of control policies on coping with COVID-19 in Guangdong Province of China. Integrating qualitative and quantitative methods to systematically analyze the effects of control policies on fighting COVID-19 with official data in Guangdong Province. Between January 19, 2020 and February 26, 2020, Guangdong Province issued 6 critical control policies to cope with COVID-19 and achieved effects in the following 3-phase. Phase 1: from January 19 to February 7, 2020, Guangdong Province issued the following 4 policies: activating the first-level response to public health emergencies; holding press conferences during the epidemic; carrying out grid investigation; and taking the lead in covering the treatment expenses of suspected patients in basic medical insurance. In this phase, the number of confirmed cases increased rapidly and the number of recovered cases increased gradually. Phase 2: from February 8 to 14, Guangdong Province issued the following 2 polices: applying Toujie Quwen granules to 30 designated hospitals and launching a registration and report system for the sale of fever and cough drugs. In this phase, the growth trend of confirmed cases had slowed down on February 10 and then increased slowly on February 14. The number of recovered cases increased rapidly on February 10 and then increased rapidly on February 14. Phase 3: from February 15 to 26, the increase number of confirmed cases was a small in magnitude on February 20 and then increased slowly on February 26. The number of recovered cases increased rapidly on February 20 and then increased rapidly on February 26. Guangdong Province implemented 6 control policies in 3-phase and finally successfully defeated the COVID-19. In the first phase, the first 4 control policies showed initial effects on COVID-19 epidemic control. In the second phase, the last 2 control policies greatly contributed to containing the COVID-19 epidemic. In the third phase, the 6 control policies completely overcame the COVID-19 in Guangdong Province, China.